Vietnam tourist guidebook - Belmonte, Patric; Marie-Eve-Therien (Hà Nội : Vietnam national Administration of tourism, 2000)
Tourist informations in Vietnam; Vietnamese country, custom, culture and person.
Keywords: Tourist; Tourist -- Vietnam -- Guidebook